Subcellular cadmium localization and characterization of cadmium-binding biomolecules in the leaves of eichhornia crassipes (mart.) solms. - Puzon, Juliana Janet R. Martin (Institute of Biology, College of Science, University of the Philippines Diliman, 2007)
The Cd contents in the subcellular fractions of the leaves were determined by inductively coupled plasma-atomic emission spectrometry in Eichhornia crassipes (Mart). Solms. plants grown in nutrient solutions amended with 5.0 ppm CdCl2. The cadmium-binding GSH-like peptide involved in the uptake, accumulation, and translocation of Cd were characterized using reversed phase-high performance chromatography, circular dichroism spectrophotometry, and Fourier transformed-infrared spectrometry methods.